PENGGUNAAN KATA SAPAAN BAHASA MINANGKABAU DI NAGARI KOTO SANI KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Arrasyid, Iqbal; Ermanto, Ermanto; Juita, Novia (Universitas Negeri Padang, 2019)
This study aims to describe (1) the form of kinship words, (2) the form of non-kinship greeting words, (3) the use of kinship words, and (4) the use of non-kinship greeting words in the Minangkabau language in Nagari Koto Sani District X Koto Singkarak Solok Regency used by speakers in everyday life. This study includes the type of qualitative research with descriptive methods. Sources of data from this study are oral sources from the people of Nagari Koto Sani District X Koto Solok Regency. The focus of this research is the Minangkabau language greeting in Nagari Koto Sani District X Koto Singkarak Solok Regency. Data collection is done by using the refer and proficient method. The steps in this study are transcribing the recorded data into written language, identifying data in accordance with the aspects studied, classifying research data by creating tables based on the aspects studied, interpreting data, and concluding data based on the results of the study. The results obtained in this study are First, the greeting of the nuclear family with 48 greeting words and broad family kinship words with 64 greeting words. Second, the word non-friendship greeting said non-religious friendship words there are 12 words of greeting, the word non-traditional friendship greeting there are 8 words of greeting, the word non-friendship address is 14 greeting words, and the word non-general address greetings are 15 greeting words.Keywords : kata sapaan, bahasa Minangkabau, Nagari Koto Sani